Destination Branding of Marine Ecotourism in Trenggalek Regency: A Study on Kili-Kili Beach Turtle Conservation - Rohmatin Alfianistiawati; Bararah M, Hasna; Putra Dionchi, Pramana Herjati; Sigit Purnomo; Noer Fatanti, Megasari (Prospect Publishing, 2023)
Kili-kili Beach Turtle Conservation is a tourist destination located on the south coast of East Java, precisely in Wonocoyo Village, Trenggalek Regency. There are approximately four types of sea turtle conservation, namely hawksbill turtles, gray turtles, leatherback turtles, and green turtles. As a new tourist destination, Kili-Kili Beach has a lot of potentials but has not been well developed. Conventional promotion methods have not been able to reach the target national and foreign tourists. Therefore, a promotion and marketing strategy is needed for Kili-Kili as an education-based tourism destination through the Internet (social media). Therefore, this service activity focuses on optimizing destination branding using the AISAS model (attention, interest, search, action, and share) through social media. The methods of implementing community service activities include 1) socialization of activity programs to local communities, 2) mentoring local communities in using social media as a medium for promoting tourist attractions, 3) training and creating social media content by involving POKMASWAS Turtle Conservation. This community service activity aims to promote the existence of marine ecotourism at Taman Kili-kili Beach, Trenggalek Regency as well as a turtle biota campaign by utilizing social media as a communication channel.